DIVERSITY AND DOMINANCE INSECT PARASITOIDS OF THE BANANA SKIPPER PEST (Erionota thrax L.) IN BANANA AGROECOSYSTEMS - Hendrival Hendrival; Zulkarnain Zulkarnain; Muhammad Muaz Munauwar (JBIO: jurnal biosains (the journal of biosciences), 2022)
Banana skipper pest (Erionota thrax L., Lepidoptera: Hesperiidae) are insect pests associated with banana plants. Control his can done by using parasitoid insects. The research aimed to study to diversity and dominance of insects parasitoid associated with banana skippers at agroecosystem banana. A sample is group eggs and roll leaf banana attacked by the banana skipper as much 40 samples (20 samples of larvae and pupae) and 20 group eggs per sample area. The results showed that species parasitoid found included parasitoid eggs is Ooencyrtus erionotae (Encyrtdae), Pediobius erionotae (Eulophidae), Anastatus sp. (Eupelmidae), and Agiommatus sumatraensis (Pteromalidae). Parasitoid larval and pupal are Cotesia erionotae (Braconidae) and Brachymeria lasus (Chalcididae). The number of individuals highest found in P. erionotae and lowest on Anastatus sp.  An index diversity of 1.2832 classified as moderate and an index evenness of 0.7161 classified as high. The level of parasitization highest on species P. erionotae at 48.73%, followed by O. erionotae at 42.50%, and lowest on Anastatus sp. at 1.75%. The level of parasitization at stages larval and pupae only reached 2.78 and 6.11%.